2016
DOI: 10.1039/c5ee03149d
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped activated carbon for a high energy hybrid supercapacitor

Abstract: The present work provides a novel one-step synthesis for nitrogen-doped activated carbon. The excellent performance of the N-doped AC allows its further application in a hybrid-type supercapacitor, which utilizes a combination of the capacitor electrode and a Li-ion battery anode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
417
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 967 publications
(433 citation statements)
references
References 35 publications
15
417
0
1
Order By: Relevance
“…The C 1s XPS spectra (Fig. S3c) could be deconvoluted into three peaks: sp 2 -sp 2 C (284.0 eV), -C-N (284.9 eV), and C=O (288.0 eV) [12,15]. The N 1s core level (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The C 1s XPS spectra (Fig. S3c) could be deconvoluted into three peaks: sp 2 -sp 2 C (284.0 eV), -C-N (284.9 eV), and C=O (288.0 eV) [12,15]. The N 1s core level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S5 were used to elucidate the electronic structure of the core levels, with peaks of sp 2 C at 284.5 eV, -C-N at 285.2 eV, and C=O at 288.0 eV in the C 1s region, along with pyridinic N (398.5 eV) and pyrrolic N (400.2 eV) in the N 1s region, demonstrating the successful combination of these elements [15,22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heteroatom of N and O doping can increase the electrical conductivity, ensure more active sites, and improve the surface wettability between carbon material and electrolytes. [142][143][144] Consequently, the PGOCN electrode exhibited a high specific capacitance of 348 F g −1 in acidic electrolyte and 308 F g −1 in alkaline electrolyte at 1 A g −1 current density, respectively. Remarkably, the PGOCN materials can be directly cut into thin sheets to assemble two-electrode supercapacitor, which delivered a specific capacitance of 220 F g −1 at 0.2 A g −1 and a power density of 1.2 kW kg −1 at an energy density of 3.4 W h kg −1 as well as outstanding cycling stability after 2000 cycles.…”
Section: Wwwadvsustainsyscommentioning
confidence: 97%
“…Stoller et al [33] reported the gravimetric capacitance values of 135 and 99 F g −1 in aqueous and organic electrolytes, respectively. In addition to nitrogen doping [34], several strategies including structural and morphological modification have been developed to improve the gravimetric figure of merit of graphene-based materials. A significantly higher gravimetric performance of 298 F g −1 was observed for graphenebased materials in ionic liquids [35].…”
Section: Introductionmentioning
confidence: 99%